Participatory action research : international contexts and consequences - McTaggart, Robin (SUNY series in teacher preparation and development., 1997)
In this book the authors tell their stories of action research in their own ways, and indeed, give expression to their own cultural positioning as they draw upon their extensive experience in the field and the academy. They write in terms of their own experience, but with a collective as well as individual purpose. Contributors describe the history of participatory action research, and identify its interpretations in the diverse cultural contexts of Colombia, India, Austria, Australia, Venezuela, USA, England, Spain, Thailand, and New Caledonia. Drawing on the fields of nursing, education, community development, land reform, popular education, agriculture, and mass media, the authors describe the development of democratic research practice in quite different institutional and cultural contexts.